El principio de progresividad en el tránsito legislativo de pensión de invalidez en la jurisprudencia de la Corte Constitucional (2011)
This work aims to draw the line of decisions of the Constitutional Court concerning the principle of progressivity in terms of economic, social and cultural rights on the reforms he has introduced the Colombian legislature on the pension. Reforms are enshrined in Article 6 of Decree 758 of 1990, Article 39 of Law 100 of 1993, Article 11 of Act 797 of 2003, and Article 1 of Act 860 of 2003. Legislation which, as we shall see, contains provisions for purposes of demonstrating regressive requirements to access the right performance based.